Investigating the Prevalence and Level of Pain Experienced by Australian Farmers - Koralegedera, Indika; Skaczkowski, Gemma; Moseley, G Lorimer; Gunn, Kate M (My University, 2025)
This study evaluated the prevalence and level of pain in Australian farmers and how these compare to the general working population. We also explored factors related to the interference of pain on farmers' work. Logistic regressions were used to examine the prevalence of chronic pain and pain interference with normal work among farmers compared to the general working population, and also to examine the factors associated with pain interference in farmers. A multinomial logistic regression model was used to examine the level of bodily pain among farmers compared to the general working population. The nationally representative HILDA (Household, Income, and Labour Dynamics Australia) survey data (wave 21) was used. The final sample included 168 (1.6%) farmers and 10 318 (98.4%) people in the general working population. There was a higher prevalence of chronic pain (p < 0.001), higher levels of bodily pain (p < 0.001), and pain interference with normal work (p < 0.001) in farmers than in the general working population. Age, gender, Body Mass Index (BMI), education level, remoteness, and personal social cohesion were not associated with pain interference with normal work in farmers. The prevalence of chronic pain, level of bodily pain, and pain interference with normal work in Australian farmers is higher than the general working population. However, information is lacking on the factors that influence pain for this unique group. Further exploration is needed into why factors that are commonly associated with pain are not associated with pain in the farming population.
The Australian Journal of Rural Health
Keywords: agriculture; biopsychosocial; chronic pain; farm; pain; rural; Health and wellbeing